O PENSAMENTO COMPUTACIONAL NO ENSINO FUNDAMENTAL I: SABERES ARTICULADOS ENTRE COMPUTAÇÃO E ARTES VISUAIS: COMPUTATIONAL THINKING IN ELEMENTARY SCHOOL: ARTICULATED KNOWLES BETWEEN COMPUTING AND VISUAL ARTS (Revista Contexto & Educação, 2021)
This article investigates the potential of teach Computer Science with an emphasis on Computational Thinking, articulated with Visual Arts in Elementary Education. The activities resulted from the Supervised Internship in Computer Science, with action research as a guiding methodology and Computer Science Unplugged, as the set of techniques that enabled actions in the context of a public school of Salvador/BA. The results intensify the need for the presence of Computer Science in the school, especially articulated with the existing curricular components; in addition to demonstrating that it is possible to develop actions that involve computational thinking articulated with other knowledge areas, in addition to the exact sciences.